2011
DOI: 10.1007/s12519-011-0303-7
|View full text |Cite
|
Sign up to set email alerts
|

Non-Hodgkin lymphoma in childhood and adolescence: frequency and distribution of immunomorphological types from a tertiary care center in South India

Abstract: The distribution of different subtypes of lymphoma in pediatric and adolescent NHL in India differs considerably from that in western countries and other eastern countries.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
7
4

Year Published

2011
2011
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(20 citation statements)
references
References 38 publications
9
7
4
Order By: Relevance
“…Extranodal sites were observed in 84.1% of cases in this cohort. This trend is in accordance with the results found in the literature [33,34]. However, the prevalence of extranodal NHL in our series was slightly high in comparison with Asiatic series where the prevalence varies from 16 to 40% [34,35].…”
Section: Non-hodgkin Lymphomas and Children supporting
confidence: 93%
“…Extranodal sites were observed in 84.1% of cases in this cohort. This trend is in accordance with the results found in the literature [33,34]. However, the prevalence of extranodal NHL in our series was slightly high in comparison with Asiatic series where the prevalence varies from 16 to 40% [34,35].…”
Section: Non-hodgkin Lymphomas and Children supporting
confidence: 93%
“…Our approach to identify a large number of new SNPs and to determine their MAF was shown to be a very efficient, cost effective approach in the design of the chip. Although, previous results [6,15] had already shown that the conversion rate of a large proportion of the SNPs identified by Wong et al [5] was very high, the conversion rate of the SNPs identified by our approach surpassed those identified by Wong et al [5]. Of the new SNPs identified in this study, more than 96% could be validated, whereas only 86% of the SNPs present in dbSNP could be validated.…”
Section: Discussioncontrasting
confidence: 63%
“…Nevertheless, numerous studies have used smaller scale SNP assays in chicken, in particular based on Illumina's GoldenGate assay [6-9]. These studies have clearly demonstrated the high validation rate of SNPs identified by Wong et al [5].…”
Section: Introductionmentioning
confidence: 99%
“…The proportion of T-cell NHL is significantly higher in the Korean pediatric and young adult population (28), Japan (29) and India (19,26), while the frequency of TLL was found to be low in Saudi Arabia (8%), Pakistan (8%) and nearly the same results were obtained from the UK (19%) and Germany (16.1%) (23,24).…”
Section: Discussionmentioning
confidence: 81%